Meta-analysis of the effect of probiotics or synbiotics on the risk factors in patients with coronary artery disease - Lei, Yunzhen; Xu, Min; Huang, Nanqu; Yuan, Zhengqiang (Frontiers in Cardiovascular Medicine, 2023)
Objective: To study the effect of probiotics or synbiotics on risk factors for coronary artery disease (CAD) in the context of conventional drug therapy for CAD.Methods: Literature on probiotics or synbiotics for the treatment of CAD was collected from PubMed, Scopus, Web of Science, Embase, and Cochrane Library. The search period was until November 1, 2022, when the database was created. The included literature consisted of randomized controlled trials (RCTs) of probiotics or synbiotics for CAD, and meta-analysis was performed using Stata 14 software and RevMan 5.4 software.The meta-analysis explored the effect of probiotics or synbiotics on risk factors for coronary artery lesions in a treatment setting with conventional medications for CAD. After a rigorous literature screening process, ten studies were finally included for data consolidation to objectively evaluate the effect of probiotics or synbiotics on coronary lesions. The results of this study showed that the addition of probiotics or synbiotics to conventional medications for CAD reduced the levels of LDL-C [WMD -9.13 (-13.17, -5.09)], FPG [WMD -13.60 (-23.57, -3.62)], hs-CRP [SMD -0.60 (-0.83, -0.37)], and increased the levels of HDL-C [WMD 1.94 (0.32, 3.57)], NO [WMD 5.38 (3.23, 7.54)], but did not affect TG [WMD -13.41 (-28.03, 1.21)], SBP [WMD -0.88 (-3.72, 1.96)], and DBP [WMD -0.21 (-2.19, 1.76)].Adding probiotics or synbiotics to conventional medications for CAD may improve patient prognosis.